Extent of Influence of Using AI Chatbots in the Writing Skills of BSE Students of Pangasinan State University – Lingayen Campus - Austria, Fiona Zoe; Camagay, Easter Bea Amor; Domasing, Monica; Gelido, Andrew; Libatique, Carl Vincent; Cabutotan, Vladimir Marie (Southeast Asian Journal of Science and Technology, 2023)
This study was conducted to determine the extent of influence of using AI Chatbots in the writing skills of BSE Students of Pangasinan State University – Lingayen Campus. The time frame of the study is one (1) semester, from the period of February to June 2023. In order to distinguished the primary concern of the study, the Descriptive Method was employed using the statistical treatment of data wherein the weighted mean was used to determine the frequency and percentage distribution, also t-test was used to identify if there is a significant difference between the Reliability of AI Chatbots used by BSE Students and the Extent of Influence of Using AI Chatbots in the Writing Skills of BSE Students of Pangasinan State University – Lingayen Campus. The researchers conducted a pre-survey to determine who among the BSE Students are using AI chatbots, and the total population of students who are using AI chatbots are three hundred forty-four. The researchers used the Slovin’s Formula to distinguished the total number of respondents that is one hundred eighty-five. The findings disclosed that the majority of BSE students at Pangasinan State University – Lingayen Campus are using AI chatbots. As to the AI Chatbots that were being used, majority of the respondents used Grammarly, next is Quillbot, and the ChatGPT. On the reliability of AI chatbots used by BSE students of Pangasinan State University – Lingayen Campus, students relied more on using AI chatbots to enhance their vocabulary. While on the extent of influence of using AI chatbots on the writing skills of the BSE students, Grammar and Vocabulary has the highest weighted mean because it provides students the appropriate spelling, punctuation, and capitalization, and also it provides vocabularies that are suited to their reading and understanding level. However, the statistical analysis involving independent t-test to compare t-statistic outcomes and the significant difference for a one tailed test shows that there is no significant difference between the reliability of AI chatbots used by the BSE Students and the extent of influence of using AI chatbots on the writing skills of BSE students at Pangasinan State University – Lingayen Campus.